2022
DOI: 10.1002/anie.202210466
|View full text |Cite
|
Sign up to set email alerts
|

Missing‐linker Defects in Covalent Organic Framework Membranes for Efficient CO2 Separation

Abstract: Covalent organic framework (COF) membranes with tunable ordered channels and free organic groups hold great promise in molecular separations owing to the synergy of physical and chemical microenvironments. Herein, we develop a defect engineering strategy to fabricate COF membranes for efficient CO 2 separation. Abundant amino groups are in situ generated on the COF nanosheets arising from the missing-linker defects during the reactive assembly of amine monomer and mixed aldehyde monomers. The COF nanosheets ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…Overcoming the limitations of polymeric membranes, separation membranes constructed by two-dimensional (2D) materials have exhibited unique attributes in precise molecular sieving owing to their unique nacre-like structures and ultrafast mass transport. As typical 2D materials, graphene-based membranes consisting of an atom-thick 2D carbon lattice and oxygen functional groups have emerged as candidates for nanofiltration due to unimpeded water permeation, excellent chemical resistance, easy solution processability, and mechanical strength. Functionalized 2D membranes with advanced performances have achieved great progress and shown potential in many applications. Recently, several pioneering works have focused on developing polymer-decorated 2D membranes to modulate the permeation of water and ion molecules by external stimuli such as pH, gas, light, and temperature. However, most previous attempts were based on modulating the molecular configuration or surface hydrophilicity of graphene-based membranes. , Moreover, similar to the polymer-based membranes, the response of polymer-decorated graphene-based membranes often takes tens of minutes (>30 min) to respond to external factors and restore to the original state, owing to the diffusion of signal chemicals and the relaxation of polymer chains. Therefore, fast, reversible, and remote control of graphene-based membranes are highly desired in practical applications. Zhou et al developed a fast-response graphene oxide (GO) based membrane to electrically control water permeation by introducing conductive filaments via electrical breakdown and ionizing the water cluster within the 2D capillary . Meanwhile, Li et al demonstrated a nanoporous graphene-based membrane to accelerate ion diffusion by modulating the interfacial electrical double layer under an external electrostatic field .…”
mentioning
confidence: 99%
“…Overcoming the limitations of polymeric membranes, separation membranes constructed by two-dimensional (2D) materials have exhibited unique attributes in precise molecular sieving owing to their unique nacre-like structures and ultrafast mass transport. As typical 2D materials, graphene-based membranes consisting of an atom-thick 2D carbon lattice and oxygen functional groups have emerged as candidates for nanofiltration due to unimpeded water permeation, excellent chemical resistance, easy solution processability, and mechanical strength. Functionalized 2D membranes with advanced performances have achieved great progress and shown potential in many applications. Recently, several pioneering works have focused on developing polymer-decorated 2D membranes to modulate the permeation of water and ion molecules by external stimuli such as pH, gas, light, and temperature. However, most previous attempts were based on modulating the molecular configuration or surface hydrophilicity of graphene-based membranes. , Moreover, similar to the polymer-based membranes, the response of polymer-decorated graphene-based membranes often takes tens of minutes (>30 min) to respond to external factors and restore to the original state, owing to the diffusion of signal chemicals and the relaxation of polymer chains. Therefore, fast, reversible, and remote control of graphene-based membranes are highly desired in practical applications. Zhou et al developed a fast-response graphene oxide (GO) based membrane to electrically control water permeation by introducing conductive filaments via electrical breakdown and ionizing the water cluster within the 2D capillary . Meanwhile, Li et al demonstrated a nanoporous graphene-based membrane to accelerate ion diffusion by modulating the interfacial electrical double layer under an external electrostatic field .…”
mentioning
confidence: 99%
“…A brief timeline of the recent developments of COF-based membranes for CO 2 separation. [54][55][56][57][58][59][60][61][62] Reproduced with permission. [54] Copyright 2016, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…[61] Copyright 2021, Elsevier B.V. Reproduced with permission. [62] Copyright 2022, Wiley-VCH. mixed gases are described, including CO 2 /CH 4 , CO 2 /H 2 , CO 2 /N 2 , and CO 2 /He (Section 4).…”
Section: Figurementioning
confidence: 99%
“…Due to their unique covalent structure, they possess the fantastic characteristics of low density, high thermal stability, large specific surface area, and easy functionalization. Since Yaghi reported the pioneering investigation on COF in 2005, COFs have attracted increasing attention due to their unique covalent skeletons, inherent porosities, high thermal stability, and easy functionalization, which are widely used in gas adsorption, 84,85 photoelectric sensing, [86][87][88] catalysis, [89][90][91] and energy storage. 92,93 However, there are very restricted reports on viologen-based COFs, and some bipyridine-based COFs have demonstrated their unique advantages.…”
Section: Viologen-based Cofsmentioning
confidence: 99%